Acquisition of omnidirectional stereoscopic images and videos of dynamic scenes: a review - Gurrieri, Luis E.; Dubois, Eric (Université d'Ottawa | University of Ottawa, 2013)
Different camera configurations to capture panoramic images and videos are commercially available today. However, capturing omnistereoscopic snapshots and videos of dynamic scenes is still an open problem. Several methods to produce stereoscopic panoramas have been proposed in the last decade, some of which were conceived in the realm of robot navigation and three-dimensional (3-D) structure acquisition. Even though some of these methods can estimate omnidirectional depth in real time, they were not conceived to render panoramic images for binocular human viewing. Alternatively, sequential acquisition methods, such as rotating image sensors, can produce remarkable stereoscopic panoramas, but they are unable to capture real-time events. Hence, there is a need for a panoramic camera to enable the consistent and correct stereoscopic rendering of the scene in every direction. Potential uses for a stereo panoramic camera with such characteristics are free-viewpoint 3-D TV and image-based stereoscopic telepresence, among others. A comparative study of the different cameras and methods to create stereoscopic panoramas of a scene, highlighting those that can be used for the real-time acquisition of imagery and video, is presented.
Keywords: stereoscopic panoramas; stereoscopic cameras; catadioptric cameras; multiple cameras; omnistereo based on panoramic sources; sequential acquisition of images; image mosaic; acquisition; dynamic scenes; panoramas; virtual reality; free-viewpoint; navigation; virtual environments; omnistereo; stereoscopy